Calculate: ((2x^3-4x^2-3x-6))/((x+3))

Expression: $\frac{(2x^{3}-4x^{2}-3x-6)}{(x+3)}$

Divide $ \frac{2x^{3}-4x^{2}-3x-6}{x+3}:{\quad}\frac{2x^{3}-4x^{2}-3x-6}{x+3}=2x^{2}+\frac{-10x^{2}-3x-6}{x+3}$

$=2x^{2}+\frac{-10x^{2}-3x-6}{x+3}$

Divide $ \frac{-10x^{2}-3x-6}{x+3}:{\quad}\frac{-10x^{2}-3x-6}{x+3}=-10x+\frac{27x-6}{x+3}$

$=2x^{2}-10x+\frac{27x-6}{x+3}$

Divide $ \frac{27x-6}{x+3}:{\quad}\frac{27x-6}{x+3}=27+\frac{-87}{x+3}$

$=2x^{2}-10x+27+\frac{-87}{x+3}$

Simplify

$=2x^{2}-10x+27-\frac{87}{x+3}$